Estimando y contrastando la extensión de las formaciones vegetales microtermales del Perú de inicios del siglo XX - Zelada Gárate, Humberto; Reynel-Rodríguez, Carlos Augusto (Pontificia Universidad Católica del Perú, 2023)
Augusto Weberbauer published, in 1922, the first vegetation map of Peru, where he showed and described twenty-five plant formations, grouped into six categories, considering altitudinal ranges defined according to their temperature. Within these categories are the microthermal formations that are generally found above 3400 masl and have a wide latitudinal distribution throughout the Peruvian Andes. To revalue that historical map, we present, firstly, the results of digitalization and estimation of extension of the four microthermal vegetation formations identified by Weberbauer, and secondly, the findings of cartographic contrasting between these microthermal formations, and the high Andean vegetation covers as classified in the most updated map on this subject. Weberbauer mapped an area of 183.445,30 km² for the four microthermal vegetation formations: typical high Andean formations (61,67%); microthermal herbaceous steppe (17,93%); microthermal tolar (17,47%); glaciers and perpetual snow (2,93%). Likewise, a cartographic comparison showed that 63,92% of the territory currently occupied by high Andean vegetation cover in Peru is coincident with that mapped by Weberbauer as microthermal vegetation formations. These results contribute to the understanding of the evolution of these formations, which are under climate change and anthropogenic pressures.

Augusto Weberbauer publicó en 1922 el primer Mapa de Vegetación del Perú, en el que representó y describió 25 formaciones vegetales, las cuales agrupó en seis categorías, considerando ámbitos altitudinales definidos en función de su temperatura. Dentro de esas categorías están las formaciones microtermales que, generalmente, se encuentran por encima de los 3400 msnm y tienen amplia distribución latitudinal a lo largo de los Andes peruanos. En aras de revalorizar aquel mapa histórico, en primer lugar, se presentan los resultados de la digitalización y estimación de la extensión de las cuatro formaciones vegetales microtermales identificadas por Weberbauer y, en segundo lugar, se exponen los hallazgos del contraste cartográfico realizado entre dichas formaciones microtermales y las coberturas vegetales altoandinas clasificadas en el mapa más actual en el Perú sobre esta temática. En ese sentido, se aprecia que el investigador alemán cartografió una extensión de 183.445,30 km² para el conjunto de las cuatro formaciones vegetales microtermales: formaciones típicas altoandinas (61,67%); estepa herbácea microtérmica (17,93%); tolar microtérmico (17,47%); los glaciares y la nieve perpetua (2,93%). Asimismo, en la comparación cartográfica se observó que el 63,92% del territorio que actualmente ocupan las coberturas vegetales altoandinas del Perú coincide con lo cartografiado e identificado por Weberbauer como formaciones vegetales microtermales. Estos resultados contribuyen a comprender la evolución de este tipo de formaciones vegetales, las cuales están sufriendo una fuerte presión por la sumatoria del cambio climático y los impactos antrópicos.
Estimating and contrasting the extent of microthermal plant formations in early 20th century Peru
Keywords: Geographical Information Systems; Natural history; Peruvian Andes; Phytogeography; Vegetation maps; Andes peruanos; Fitogeografía; Historia natural; Mapa de vegetación; Sistema de Información Geográfica; https://purl.org/pe-repo/ocde/ford#5.07.00